The Effect of the Reciprocal Teaching Model on Learning Outcomes in Islamic Religious Education - Wenas, Fitri Ramadhani; Surikno, Heri; Fitriani, Saparia; Rahmi, Azvi; Helena, Helena (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2025)
This research is motivated by students who are not yet active in learning. Because the learning process is still conventional, this study aims to determine the Reciprocal Teaching model, Islamic Religious Education learning outcomes, and the influence of the Reciprocal Teaching model on Islamic Religious Education learning outcomes in class V. This research method is quantitative research using an experimental approach with a randomized posttest only control group design. The population is students in classes V-A and V-B, as well as being sampled. The data collection technique is a test, which seeks validity, homogeneity, reliability, discrimination power, and question difficulty index. While the prerequisite analysis test, namely using the normality test using the Lilifors test, the homogeneity test using the F test, and the hypothesis test using the t test. The final test results obtained an average value of the experimental class 80.75 and the control class 68.05, with a difference of 12.7. The results of the t test obtained tcount is 11.55. And t table with degrees of freedom dk 42 from the t table (0.950) (42) = 2.018. The hypothesis testing criteria are to accept Ho if t count <t table. In this study t count > t table, meaning reject Ho and accept Ha. It can be concluded that the Reciprocal Teaching model has a positive effect on PAI learning outcomes in class V of State Elementary School 17 2X11 Kayutanam.